Emerging Ultrahigh‐Density Single‐Atom Catalysts for Versatile Heterogeneous Catalysis Applications: Redefinition, Recent Progress, and Challenges. Issue 6 (15th April 2022) - Li, Zesheng; Li, Bolin; Hu, Yifan; Liao, Xichun; Yu, Huiqing; Yu, Changlin
Abstract : In recent years, single‐atom catalysts (SACs) with high metal loading have emerged in different heterogeneous catalysis fields and shown extraordinary catalytic properties. When there are enough coordination atoms (or functional groups) on the supports, it is possible to achieve a limit monolayer atom loading on the surface of supports with ultrahigh atom density (5–15 atoms nm −2 ) and extremely close site distance (0.2–0.5 nm), by using appropriate synthesis methods and procedures. These high‐density metal atoms usually have no or less metal bonds, which are mostly isolated by support atoms to form 3D foam‐like atomic constructions. Herein, a new notion of metal atomic foam catalysts (AFCs) is propsed to redefine these ultrahigh‐density SACs accommodated by specific supports. This new paradigm of 3D atomic construction for SACs has potential significance for both theoretical research and industrial applications. The latest major advancements in the controllable synthesis of AFCs on various supports (e.g., polymer, carbon, and metallic compound) via different methods (bottom‐up or top‐down approaches) are summarized. The latent catalytic principles and typical application cases of AFCs are emphasized in a wide range of heterogeneous catalysis fields (e.g., thermocatalysis, photocatalysis, electrocatalysis, etc.). The challenges and prospects of this newly 3D ultrahigh‐density AFCs materials in practical industrial application are pointed out as well. Abstract : The fundamental catalytic principles and recent catalysis progress of metal atomic foam catalysts (AFCs) are systematically summarized for a wide range of heterogeneous catalysis fields (including thermocatalysis, photocatalysis, electrocatalysis, etc.).